Pengaruh Pendekatan Pembelajaran STEM terhadap Keterampilan Abad 21 di Educourse.id - Hanum Arumningtyas; Ilyas Ilyas (Universitas Hamzanwadi, 2025)
Critical thinking skills are highly essential in the learning process, especially considering that critical thinking is one of the key skills being developed in the 21st century. This study aims to describe the influence of the STEM learning approach on 21st-century skills at Educourse.id. The method used is a quantitative method with a pre-experimental one-group pretest-posttest design. The population in this study consists of all Educourse.id course participants located in BSD Tangerang who participated in the STEM-based learning program during 2024, using purposive sampling technique. The results showed that there was a significant difference between the pre-test and post-test scores, with a significance result of 0.000, which is smaller than the alpha value of 0.05. The calculated t-value (-7.708) was less than the critical t-value (-2.35), leading to the decision to reject H0. This means that there is a significant difference between the pre-test and post-test scores.